2018
DOI: 10.1248/cpb.c17-00740
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study on Complex Conformations of Aβ<sub>42</sub> Peptides on a GM1 Ganglioside-Containing Lipid Membrane

Abstract: Aggregation and complex formation of amyloid beta (Aβ) peptides on a neuronal cell membrane is a hallmark of neuro-disturbance diseases. In this work, we performed molecular dynamics (MD) simulations to investigate the initial stage of interactions of multiple Aβ 42 peptides on a GM1 ganglioside-containing membrane that mimics a micro-domain on the neuronal cell surface. Conformational changes of Aβs due to adhesion on the membrane and subsequent molecular interactions among the Aβs were monitored. It was sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…Six of them are negatively charged, and the other three are positively charged residues. , An important observation in the present simulation was that Aβ 40 was deeply inserted into the head group region of the lipid membrane, as shown in Figure . This insertion was not observed in the case of Aβ 42 in our previous study. , This means that Aβ 40 was more likely than Aβ 42 to have a strong interaction with the inside of the membrane. The results of a study suggested the possibility of Aβ creating a pore or channel for ions and reactive oxygen species to access the inside of the membrane and attack the nonpolar lipid molecules .…”
Section: Discussioncontrasting
confidence: 51%
“…Six of them are negatively charged, and the other three are positively charged residues. , An important observation in the present simulation was that Aβ 40 was deeply inserted into the head group region of the lipid membrane, as shown in Figure . This insertion was not observed in the case of Aβ 42 in our previous study. , This means that Aβ 40 was more likely than Aβ 42 to have a strong interaction with the inside of the membrane. The results of a study suggested the possibility of Aβ creating a pore or channel for ions and reactive oxygen species to access the inside of the membrane and attack the nonpolar lipid molecules .…”
Section: Discussioncontrasting
confidence: 51%
“…All of the structures were visualized using PYMOL Chimera software version 1 6 . The calculation procedure was almost the same as that in our previous work 42-44 with neutralizing, antibodies were separated from SARS-CoV-2 S-RBD into individual files for docking simulation. The root-mean-square deviation (RMSD) was calculated to evaluate the change in the geometric structure of S-RBD after docking by using backbone atoms.…”
Section: Methodsmentioning
confidence: 99%
“…All of the structures were visualized using PYMOL Chimera software version 1 [31]. The calculation procedure was almost the same as that in our previous work [32][33][34] with neutralization. Antibodies were separated from SARS-CoV-2 S-RBD into individual files for docking simulation.…”
Section: Construction Of the Computational Modelmentioning
confidence: 99%